A natureza das críticas de Mivart ao papel da seleção natural de Darwin na origem das espécies: uma reconsideração histórica da controvérsia - Almeida Filho, Enézio Eugênio de (2008)
This research follows the line of History and Theory of Science that has as a goal to explain the construction of scientific thought by discussing the foundation of hypotheses and theories within their historical contexts. The goal of this thesis is to analyze Mivart´s critiques and Darwin´s answers, and to verify if they were scientifically well formulated and based considering the scientific context of that time. The reason for writing this work is an attempt to fill a gap in the History of Science about the scientific controversy between Mivart and Darwin on the role of natural selection in the origin of species. This work´s hypotheses are two: that Mivart´s critiques, despite being religiously motivated, were plausible scientifically, and that Darwin answered them fully. This research analyzes the primary sources of Mivart (Genesis of species) and Darwin's Origin of Species, and other secondary sources. The result reached was that Mivart´s critiques were indeed scientific, and that Darwin answered them according to the evidences and scientific knowledge then available